Characterization of a New M4 Metalloprotease With Collagen-Swelling Ability From Marine Vibrio pomeroyi Strain 12613 - Wang, Yan; Liu, Bai-Xue; Cheng, Jun-Hui; Su, Hai-Nan; Sun, He-Min; Li, Chun-Yang; Yang, Liuyan; Shen, Qing-Tao; Zhang, Yu-Zhong; Zhang, Xia; Chen, Xiu-Lan (Frontiers in Microbiology, 2020)
The ocean harbors a variety of bacteria which contain huge protease resources and offer a great potential for industrial and biotechnological applications. Here, we isolated a protease-secreting bacterium Vibrio pomeroyi strain 12613 from Atlantic seawater and purified a protease VP9 from strain 12613. VP9 was identified as a metalloprotease of the M4 family. VP9 could hydrolyze casein and gelatin, but not elastin and collagen. With gelatin as the substrate, VP9 showed the highest activity at 40oC and pH 6.0-8.0. It was stable at temperatures of 50oC and less and in the range of pH 5.0-11.0. VP9 also had good tolerance to NaCl, nonionic detergents, and organic solvent methanol. Unlike other M4 metalloproteases, VP9 has distinct collagen-swelling ability, and its collagen-swelling effect was concentration-dependent. The relative expansion volume of collagen increased by approximately 8 fold after treatment with 10 µM VP9 at 37oC for 12 h. The collagen-swelling mechanism of VP9 on bovine-insoluble type I collagen was further studied. Atomic force microscopy observation and biochemical analyses showed that VP9 can degrade proteoglycans in collagen fibers, resulting in the release of collagen fibrils from collagen fibers and the swelling of collagen fibers. In addition, VP9 can degrade glycoproteins, a noncollagenous constituent interacting with collagen in skin. The characters of VP9 that has sufficient specificity towards proteoglycans and glycoproteins but no activity towards collagen suggest its promising potential in the unhairing and fiber-opening processing in leather industry.